The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1287/opre.2019.1944
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note—There’s No Free Lunch: On the Hardness of Choosing a Correct Big-M in Bilevel Optimization

Abstract: There's No Free Lunch in Bilevel Optimization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Where α is a binary variable and M is a large enough constant. However, choosing an appropriate value for M is important for numerical stability, but can be a challenging task in itself [22].…”
Section: A Linearization Methodsmentioning
confidence: 99%
“…Where α is a binary variable and M is a large enough constant. However, choosing an appropriate value for M is important for numerical stability, but can be a challenging task in itself [22].…”
Section: A Linearization Methodsmentioning
confidence: 99%
“…The resulting problem is an exact reformulation of the original problem, if the M parameters are appropriately chosen. However, as pointed out in [29], this is a non-trivial task. In our case, the nonlinearities in the objective function are not further linearized as in [2], because Gurobi's noncovnex solver handled the resulting MINLP efficiently and it guarantees global optimality.…”
Section: Bi-level Formulation Of the Optimal Bidding Problemmentioning
confidence: 97%
“…In [46], it is shown that wrong big-Ms can lead to suboptimal solutions or points that are actually bilevel infeasible. Unfortunately, even verifying that the bounds are correctly chosen is, in general, at least as hard as solving the original bilevel problem; see [37]. Thus, if possible, big-Ms should be derived using problem-specific knowledge.…”
Section: Convexification Of the Strong-duality Constraintmentioning
confidence: 99%